RANCANG BANGUN PROTOTYPE PEMBANGKIT LISTRIK TENAGA ARUS LAU: Rancang Bangun Prototype Pembangkit Listrik Tenaga Arus Laut - Izzah, Nurul; Syafi’i, Andi Muhammad; Akbar, Fery; Akbar, Muhammad; Alham, Rani (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2024)
Renewable electricity from the sea is one of the efforts in the search for energy amid the Fossil fuel crisis. In this journal, we design a prototype PLTAL with the initial stage is determining the test parameters on the prototype so that it can be processed and analyzed data, then carried out Assembling PLTAL prototype design, and finally the prototype testing. Based on the results of the PLTAL prototype test with water volume parameters, the power value P = 0.707 Watt, with a water discharge rate of 0.101 x 10-3 m3 / and the diameter of the turbine diameter d = 0.08 m and with a turbine efficiency of 0.15554 Watt. So from this experiment it can be seen that the volume of water affects the size of the power generated by our prototype.